2020
DOI: 10.1111/twec.12969
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐country distancing, globalisation and the coronavirus pandemic

Abstract: Originating in China, the coronavirus has reached the world at different speeds and levels of strength. This paper provides an initial understanding of some driving factors and their consequences. Since transmission requires people, the human factor behind globalisation is essential. Globalisation, a major force behind global well‐being and equality, is highly associated with this factor. The analysis investigates the impact globalisation has on the speed of initial transmission to a country and on the scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 27 publications
5
70
0
2
Order By: Relevance
“…In recent studies (33,34), globalisation has been shown to be positively linked to the COVID -19 cases in that more globalised countries experience higher exposure to COVID-19 outbreaks.…”
Section: Different Underlying Processes Characterise Types Of Spatialmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent studies (33,34), globalisation has been shown to be positively linked to the COVID -19 cases in that more globalised countries experience higher exposure to COVID-19 outbreaks.…”
Section: Different Underlying Processes Characterise Types Of Spatialmentioning
confidence: 97%
“…Among its many related impacts, globalisation has increased the speed of global disease diffusion, as public health studies have repeatedly acknowledged (23,35). One study (34) focused on the initial spread of COVID-19 based on Johns Hopkins University (JHU) data for March 16 th , 2020 and found that more economically globalised countries were affected faster. COVID-19 has rapidly spread via international air (36) and sea (37) travel connecting countries with high levels of tourism and trade.…”
Section: Different Underlying Processes Characterise Types Of Spatialmentioning
confidence: 99%
“…the same day two Chinese tourists tested positive for COVID-19 and were hospitalised in Rome), the national government implemented the first restrictive measures: it declared the state of emergency and it blocked all flights to and from China. As a recent study by Zimmermann et al (2020) highlighted, the contagion speed of the novel coronavirus seems to be also favoured by globalisation and, despite measures adopted in Italy, on February 21, a cluster of cases was discovered in the Lombardy region. Despite the attempt of the Italian government to isolate the cluster declaring 'red areas' all municipalities counting COVID-19 infected, the virus has spread throughout the country and on 23 February, Italy became the European country with the highest number of registered positive cases.…”
Section: Covid-19 Outbreak In Italymentioning
confidence: 99%
“…In recent studies (33,34), globalisation has been shown to be positively linked to the COVID-19 cases in that more globalised countries experience higher exposure to COVID-19 outbreaks. Among its many related impacts, globalisation has increased the speed of global disease diffusion, as public health studies have repeatedly acknowledged (23,35).…”
Section: Introductionmentioning
confidence: 97%
“…Among its many related impacts, globalisation has increased the speed of global disease diffusion, as public health studies have repeatedly acknowledged (23,35). One study (34) focused on the initial spread of COVID-19 based on Johns Hopkins University (JHU) data for March 16th, 2020 and found that more economically globalised countries were affected faster. COVID-19 has rapidly spread via international air (36) and sea (37) travel connecting countries with high levels of tourism and trade.…”
Section: Introductionmentioning
confidence: 99%